2019
DOI: 10.1007/s40261-019-00750-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Teriflunomide Compared to Interferon Beta-1b for Relapsing Multiple Sclerosis Patients in China

Abstract: Background and Objective Teriflunomide is a once-daily oral immunomodulatory agent approved in 80 countries for the treatment of patients with relapsing multiple sclerosis (RMS). The study objective was to estimate the cost effectiveness of teriflunomide (14 mg tablet, daily) versus interferon beta-1b (250 mcg subcutaneous injection, every other day) among RMS patients from the Chinese healthcare system perspective. Methods A Markov model with annual cycles and a lifeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Overall, the most common source of the natural history data was the London Ontario data set ( n = 33). Another source was the British Columbia data set, which was sourced by 13 studies [ 42 , 46 , 77 , 78 , 119 121 , 124 , 144 , 151 154 ]. Among these, four studies [ 42 , 119 , 144 , 152 ] coupled the data with the London Ontario data set, seven studies supplemented the London Ontario data set with a Sweden registry data set, three of which were US studies [ 71 , 137 , 155 ], while the remaining were studies from Europe ( n = 2) [ 50 , 76 ] and Iran ( n = 2) [ 43 , 156 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the most common source of the natural history data was the London Ontario data set ( n = 33). Another source was the British Columbia data set, which was sourced by 13 studies [ 42 , 46 , 77 , 78 , 119 121 , 124 , 144 , 151 154 ]. Among these, four studies [ 42 , 119 , 144 , 152 ] coupled the data with the London Ontario data set, seven studies supplemented the London Ontario data set with a Sweden registry data set, three of which were US studies [ 71 , 137 , 155 ], while the remaining were studies from Europe ( n = 2) [ 50 , 76 ] and Iran ( n = 2) [ 43 , 156 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the seven-state Markov model, the EDSS state was grouped into few limitations in mobility (EDSS 0.0-2.5), moderate limitations in mobility (EDSS 3.0-5.5), walking aid or wheelchair required (EDSS 6.0-7.5), restricted to bed (EDSS 8.0-9.5), and death (EDSS 10 or natural causes of death). Nine studies [47,78,[119][120][121][122][123][124][125] and three HTA reports [88,97,103] constructed models consisting of 11 health states: ten EDSS states per the EDSS (EDSS 0-9) and one death state. The remaining studies had a Markov model in which the number of states varied between three and 21.…”
Section: Markov Model Health Statesmentioning
confidence: 99%
“…At the same time, this study also set up a drug withdrawal mechanism and second-line treatment with natalizumab after drug withdrawal, so that the results are closer to the real situation. Yan Xu et al [23] . conducted a cost-effect analysis of teri unomide and IFN-β1a from the perspective of Chinese medical care, and found that teri unomide has a lower cost and a higher effect, compared to IFNβ-1a.…”
Section: Discussionmentioning
confidence: 99%
“…The probability is 82%, and the probability that recurrence does not lead to hospitalization is about 18%. At the same time, adverse reactions will also lead to a decrease in the annual utility value [23] . (Table 2)…”
Section: Utilitymentioning
confidence: 99%
“…The time horizon in this study was the lifespan and the interval of the annual Markov cycles. For each one-year cycle in the model, the patients remained in their current states or were transferred to other ones, and any patient might experience relapse or death (23,24). All the probabilities of transition to other states, Annualized Relapse Rate, and the probability of death in each Expanded Disability Status Scale (EDSS) were extracted based on previously published studies and were presented in Table 1 1 (25)(26)(27)(28).…”
Section: Overview and Model Structurementioning
confidence: 99%